Celebrating Breastfeeding Week-2024; What Have We Achieved and What Can Still be Done? - Nagendra Chaudhary (Journal of Universal College of Medical Sciences, 2024)
Breastfeeding week is held in the ﬁrst week of August every year. The event is organized and supported by World alliance for breastfeeding action (WABA), World Health Organization (WHO), the United Nations Children`s Fund (UNICEF) and many ministries of health and civil society partners. It is celebrated in more than 120 countries worldwide. World breastfeeding week was ﬁrst celebrated in 1992 by WABA and is now observed in over 120 countries by UNICEF, WHO and their partners including individuals, organizations, and governments. WABA itself was formed on 14 February 1991 with the goal to re-establish a global breastfeeding culture and provide support for breastfeeding everywhere.